Perception and practice of waling exercise in morning walkers (KYAMC Journal, 2013)
Walking is the mostly preferred form of exercise for all ages. Brisk walking [5-6 kilometer per hour] for 30-60 minutes is an ideal one for a healthy person. A lot of people in urban Bangladesh do morning walk for cheering good health. This descriptive study was carried out among 208 morning walkers in Rajshahi Metropolitan area, selected purposively and was interviewed with a pre-tested close ended questionnaire for appraisal of their knowledge and practice of morning walking. The mean age of the respondents was 45.78 ± 13.01 years and majority of them (54.33%) had health problems including diabetes (35.58%). Almost all (92.30%) preferred walking in the morning. Majority respondents (64.42%) walked every day in the week and 64.90% spent one hour daily for it. Among the respondents, majority (60.58 %) had knowledge of one hour daily walking and 55.77% knew that daily walking coverage for two kilometers was the ideal. Only 3.63% of the morning walkers were found walked briskly and were scientifically correct in their practice. Most of the respondents with health problems had consulted with physicians but did not get proper guideline for walking. Physicians should advice their patients with detail about walking considering the age and the disease if they think it necessary. Health education program for acceptance of walking with correct information should be initiated and broadcast in mass media for general people.DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13264KYAMC Journal Vol.2(2) January 2012, 193-197